Anampses viridis Valenciennes 1840 (Pisces: Labridae)—a case of taxonomic confusion and mistaken extinction - Russell, Barry C.; Craig, Matthew T. (Zootaxa, 2013)
Anampses viridis Valenciennes 1840 is known from only three specimens collected from Mauritius, and despite intensive sampling, the species has not been seen or reported since it was originally described. This apparent failure to ‘rediscover’ A. viridis at Mauritius has led to speculation that it is extinct, and the species has been widely cited as an example of a marine fish extinction. Far from being extinct, Anampses viridis has been taxonomically confused and actually is the adult male (terminal phase) colour form and a junior synonym of A. caeruleopunctatus Rüppell 1829, a species that is common and widespread throughout the Indo-West Pacific region.